PREVALENSI HIPERTENSI PADA MASYARAKAT DI DESA TEMBUKU KABUPATEN BANGLI BULAN SEPTEMBER 2014 - Sri Mahadhana; Roby Paguh Tarigan; I Gede Riswandinata Karyadi (E-Jurnal Medika Udayana, 2016)
HYPERTENSION PREVALENCE OF PEOPLE IN TEMBUKU VILAGE, BANGLI REGENCY SEPTEMBER 2014 ABSTRACT Hypertension define as persistent elevation of blood pressure above normal range. Hypertension is chronic disease of cardiovascular system that can occur several severe complication including heart disease and stroke. About 40% of world population is suffering from hypertension. People who live in the rural area is very vulnerable to suffering more from hypertension due to lack of understanding and statistical information of hypertension. The shift from infectious disease to metabolic disease is happening in rural area and that should be considered as a problem and information of the real situation in rural area of hypertension should be done and to determine the risk factors of hypertension to decrease incidence of hypertension. This research is using descriptive quantitative method. Research is conducted with measurement of blood pressure from the randomly chosen 96 samples and investigation of hypertension risk factors. Risk factors such as gender, family history of hypertension, smoking habit, BMI (body mass index), physical activity, coffee consumption, and average of daily salt intake are questioned to the samples. This research found that 43% of people in Tembuku village is suffering from hypertension. Smoking and coffee consumption is considered as major risk factors in developing hypertension of people in Tembuku village